Da teoria à prática do estágio supervisionado no ensino fundamental: caminhos necessários para sua consecução - OLIVEIRA, Ronaldo do Nascimento (2023)
The Supervised Internship in Elementary Education is a mandatory component within the degree in Pedagogy. Offered in the 7th semester of the course. It allows the student to experience theorized moments in the classroom in a practical way, while building new skills and competences, confirming their vocation for teaching. In this way, this research work theoretically seeks to describe, from concrete experiences, how the Supervised Internship is developed in a practical way. It analyzes the various elements necessary for its conduction in the field of application, highlighting each of these steps. The work is an action-research, with a qualitative-quantitative approach, anchored in bibliographic research, participant observation, photographs, questionnaires and the development of pedagogical activities. The research was developed in a school in the city of Bragança/PA, it involved students and a teacher of the 5th year of elementary school. The results show the importance of systematic organization and pedagogical involvement between intern, teacher and students as essential for the success of the work and as a tool for emancipating the future educator.